IT project management : on track from start to finish - Phillips, Joseph (New York : McGraw-Hill Osborne, 2004)
Renowned IT project management expert, Joseph Phillips, again delivers an authoritative, easy-to-understand guide that delves into all CompTIA IT Project+ certification objectives. The (3z(BInside the Exam(3y (Bsections focus on the necessary topics to pass the new CompTIA exam. Each chapter features an end-of-chapter review, and the CD-ROM includes an IT Project+ practice test, plus templates and worksheets to use when managing a project. The included real-world examples that provide on-the-job insight from practicing project management professionals, and tie discussed theory to practice, make this comprehensive reference a must-have for IT staff.
Includes index.
oif 18/02/15
Loan
Keywords: Information technology; Project management